Mechanisms of acrolein induces toxicity in human umbilical vein endothelial cells: Oxidative stress, DNA damage response, and apoptosis. Issue 4 (15th December 2021) - Liu, Dan; Cheng, Ye; Mei, Xueying; Xie, Yanzhen; Tang, Zhipeng; Liu, Jianli; Cao, Xiangyu
Abstract: Acrolein is a ubiquitous environmental pollutant that produced by the incomplete combustion of cigarette smoke, forest fires, petroleum fuels, plastic materials, and cooking fumes. Inhalation is a common form of people exposure to acrolein, increasing evidence demonstrates that acrolein impairs the cardiovascular system by targeting vascular endothelial cells. However, the molecular mechanism of the cytotoxicity of acrolein exposure on vascular endothelial cells remains unclear. This work focused on the toxicity of acrolein on human umbilical vein endothelial cells (HUVECs). The molecular mechanism was studied based on oxidative stress, DNA damage response (DDR), and mitochondrial apoptosis pathways. After HUVECs were treated with 12.5, 25, and 50 μM acrolein for 24 h, cell viability, cell colony formation, mitochondrial membrane potential, and adenosine triphosphate content significantly reduced, and acrolein increased intracellular reactive oxygen species, apoptosis rate, and 8‐hydroxy‐2 deoxyguanosine (8‐OHdG) level. Furthermore, p38MAPK and c‐Jun N‐terminal kinase signaling pathways were activated in response to oxidative stress. Moreover, acrolein induced G0/G1phase arrest, promoted the expression of γ‐H2AX, activated the DDR signaling pathway (Ataxia‐Telangiectasia‐Mutated [ATM] and Rad‐3‐related/Chk1 and ATM/Chk2), and triggered the consequent cell cycle checkpoints. Finally, the protein expression of Bax/Bcl‐2 and cleaved Caspase‐3 was up‐regulated, suggesting apoptosis was induced by triggering the mitochondrial apoptosis pathway. All these results indicated that acrolein induced HUVECs cytotoxicity by regulating oxidative stress, DNA damage, and apoptosis. This study provides a novel perspective on the mechanism of acrolein‐induced cardiovascular toxicity, it will be helpful for the prevention of acrolein‐induced cardiovascular disease.